2012
DOI: 10.1177/1040638712440988
|View full text |Cite
|
Sign up to set email alerts
|

Utility of nuclear morphometry in the cytologic evaluation of canine cutaneous soft tissue sarcomas

Abstract: Abstract. Cytopathologists lack reliable criteria to distinguish neoplastic from reactive spindle cells; however, with computer-based nuclear morphometry, it is now possible to more objectively and precisely quantify differences between selected populations of cells. Forty-four cutaneous soft tissue sarcomas and 5 cases of reactive spindle cell proliferations in the dog were morphometrically analyzed with regard to median and standard deviation (SD) of nuclear area, diameter (max, min, mean), radius (max, min)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Interestingly, 2 studies utilizing cytomorphometry via digital software analysis have found that nuclear size and pleomorphism, changes often associated with malignant criteria, are greater in reactive mesenchymal processes than neoplastic cells of soft‐tissue sarcomas. These findings further exemplify the challenges of accurately assessing adequacy of surgical excision . Shaved margin sampling by the operating surgeon focuses the pathologist's assessment on specific areas of concern, but is subject to sampling error, especially given the relatively small sample size (eg, approximately 5 mm in length).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, 2 studies utilizing cytomorphometry via digital software analysis have found that nuclear size and pleomorphism, changes often associated with malignant criteria, are greater in reactive mesenchymal processes than neoplastic cells of soft‐tissue sarcomas. These findings further exemplify the challenges of accurately assessing adequacy of surgical excision . Shaved margin sampling by the operating surgeon focuses the pathologist's assessment on specific areas of concern, but is subject to sampling error, especially given the relatively small sample size (eg, approximately 5 mm in length).…”
Section: Discussionmentioning
confidence: 88%
“…The limitations of the present report center on issues related to cytology and histology of the cells at the periphery of a neoplastic lesion. Mesenchymal neoplasms such as STS may be continuous with reactive granulation tissue and cytologic distinction between reactive and neoplastic mesenchymal cells can be difficult . Differentiating reactive and neoplastic mast cells is equally problematic, although conventional morphologic distinction has been based on the presence of cellular clusters .…”
Section: Discussionmentioning
confidence: 99%
“…Cell roundness index and nuclear displacement have been identified recently as 2 novel morphometric parameters that distinguish between normal and neoplastic lymphocytes; malignant lymphocytes were less round than benign lymphocytes, and consistent eccentricity of nuclei was observed in malignant lymphocytes . The usefulness of nuclear morphometry as a diagnostic aid and prognostic indicator has been evaluated in veterinary medicine for different tumours though this technique has not been used as a routine diagnostic tool. As nuclear irregularities were commonly observed when evaluating cytologic smears, it was anticipated that at least some of the nuclear parameters would be significantly different between diagnosis and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…14 Additional morphometric studies using cytologic smears followed in the veterinary literature investigating canine mammary gland tumors [15][16][17] , canine perianal adenocarcinomas 18 , canine and feline basal cell carcinomas 19,20 , canine sebaceous carcinomas 21 , canine cutaneous squamous cell carcinomas 22 , feline mammary gland epithelial tumors 23 , canine cutaneous mast cell tumors 24 , canine ceruminous adenomas and carcinomas 25 , and canine soft tissue sarcomas. 26,27 Nuclear morphometry (NM) has even been used to evaluate epithelial cells in endometrial cytology samples as a useful tool for reproductive diagnosis in dogs. 28 Nuclear morphometry is conducted utilizing a high-quality microscope, attached to a digital camera system and computer, with sophisticated digital image analysis software.…”
mentioning
confidence: 99%
“…[15][16][17] For the assessment of canine cutaneous ceruminous and apocrine gland tumors, as well as canine anal sac gland tumors, MNA, MNP, and MND could be useful for differentiating adenomas from adenocarcinomas. 25,30,31 For canine soft tissue sarcomas (STSs) in a blinded study, no significant differences were found between nuclear morphometric parameters and histologic features used for grading of STSs (mitotic index, and tumor necrosis score) nor with the final histologic grade 26 , and in another study comparing 24 dogs diagnosed with STSs and 24 dogs with reactive connective tissue lesions (granulation tissue and dermal fibrosis), mean values for all parameters measured (MNA, MNP, MND, minimum and maximum nuclear diameter) were higher in reactive processes than STSs, but no significant difference was found between STS subtypes. 27 There are advantages in using NM for studying cytologic smears.…”
mentioning
confidence: 99%